AVAILABILITY AND UTILITY OF EDUCATIONAL E-RESOURCES IN THE LIBRARY - Lal, Dr. Pyare; Pushkar, Santosh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present research paper has been conducted with the aim of finding out the availability and utility of educational e-resources in the library of Lala Lajpat Rai Memorial and Affiliated Sardar Vallabh Bhai Patel Medical College. Under the research, data has been collected from 50 respondents through questionnaire and the findings of the research study show that despite the availability of resources in the libraries, there is a lack in the level of interest of the users and the resources that are available are not used properly by the users, hence the researcher has also presented suggestions in his research findings to the librarians to establish access to e-resources in the libraries and to the users.